Unfavorable Hormonal and Psychologic Profile in Adult Women with a History of Premature Adrenarche and Pubarche, Compared to Women with Polycystic Ovary Syndrome - Livadas, Sarantis; Bothou, Christina; Kanaka-Gantenbein, Christina; Chiotis, Dimitrios; Angelopoulos, Nicholas; Macut, Djuro; Chrousos, George P. (Hormone and Metabolic Research, 2020)
If circulating adrenal androgens levels rise before the age of 8 years in girls, this phenomenon is termed premature adrenarche (PA), while the concomitant appearance of pubic hair is called premature pubarche (PP). Girls with PA-PP display an unfavorable hormonal profile compared to their normal peers and have an increased risk of developing polycystic ovary syndrome (PCOS) features peripubertally. However, the sequelae of premature adrenarche remains unclear. We assessed metabolic, hormonal, psychologic profiles, and ovarian morphology in 21 women of mean age (±SD) 21.3±3.3 years, BMI: 23.6±4.4 kg/m2 with PA-PP, 45 women with PCOS and 26 controls, matched for age and BMI. PA-PP women displayed a favorable lipid profile compared to PCOS and controls. Insulin resistance index (HOMA-IR), however, were similar in PA-PP and PCOS women (2.09±1.42, 2.08±0.83) and higher than controls (1.13±0.49, p <0.05). Circulating androstenedione levels did not differ between PA-PP and PCOS women (0.11±0.05 vs. 0.12±0.03), but was higher than that of controls (0.02±0.0 nmol/l, p <0,05). Ovarian volume was increased in PA-PP and PCOS (11.14±3.3 vs. 10.99±4.61) compared to controls (6.74±1.83 cm3). PA-PP women had a higher score of state/trait anxiety and depressive and eating disorder symptoms than controls, with a pattern that matched that of PCOS women. Only 14% of the PA-PP group fulfilled the Rotterdam PCOS criteria. Some women with a history of PA-PP displayed hormonal and psychologic profile similar to PCOS, and accordingly a regular monitoring of these girls during adulthood is advised.
Keywords: premature adrenarche; psychologic profile; premature pubarche; insulin resistance; PCOS